2002
DOI: 10.1038/sj.onc.1205903
|View full text |Cite
|
Sign up to set email alerts
|

The human papillomavirus type 16 E6 oncogene induces premature mitotic chromosome segregation

Abstract: Expression of the human papillomavirus type 16 E6 and E7 oncogenes initiates and maintains abnormal cell replication, by interacting with the p53 and retinoblastoma (Rb) gene products. Subsequent changes in host cell gene expression, as a consequence of genetic instability, can result in progression to invasive carcinoma. In addition to previously described effects of these viral oncogenes on centrosome synthesis, primarily associated with the expression of E7, the results described herein demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…Both numerical and structural chromosomal abnormalities are a frequent feature of HPV oncoprotein expressing cells; and the expression of both E6 and E7 proteins induce mitotic abnormalities in keratinocytes [31, 33]. If, as our data indicate, the loss of the PDZ binding function of E6 causes an increase in abnormal cells in anaphase and telophase, and elevated levels of micronuclei formation, then this would lead to an increase in the frequency of chromosomal abnormalities.…”
Section: Resultsmentioning
confidence: 70%
“…Both numerical and structural chromosomal abnormalities are a frequent feature of HPV oncoprotein expressing cells; and the expression of both E6 and E7 proteins induce mitotic abnormalities in keratinocytes [31, 33]. If, as our data indicate, the loss of the PDZ binding function of E6 causes an increase in abnormal cells in anaphase and telophase, and elevated levels of micronuclei formation, then this would lead to an increase in the frequency of chromosomal abnormalities.…”
Section: Resultsmentioning
confidence: 70%
“…This is biologically relevant since in HPV-infected cells, E6 could potentially trigger the spindle checkpoint as it induces a high percentage of metaphase-lagging (misaligned) chromosomes (5,28). After treatment with nocodazole, E7-expressing PHKs and RPE1 cells showed a significant increase in polyploidy compared to vector controls (42.9% versus 10.0% in PHKs and 42.0% versus 1.0% in RPE1 cells; Fig.…”
Section: Expression Of Hpv E7 Results In Polyploidymentioning
confidence: 95%
“…, protein phosphatase 2A and p300 (Duensing and Munger, 2002;Davies et al, 2003), which leads to high genetic instability in the immortalized cells (Bernues et al, 1991;Ouellette et al, 2000;Duensing and Munger, 2002;Iftner et al, 2002;Plug-Demaggio and McDougall, 2002;Davies et al, 2003;Liu et al, 2004). In contrast, our immortal cell line (T137pRbi) showed that little genetic instability had been induced by the disruption of pRb pathway and ectopic expression of hTERT (Table 1).…”
Section: Ink4amentioning
confidence: 61%